2023
DOI: 10.3390/ma16031060
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Sound Absorption Composite Materials Developed Using Flax Fiber, Sphagnum Moss, Vermiculite, and Sapropel

Abstract: To address the need to reduce consumption and pollution in the industrial sector, composite materials were created using a new type of raw materials—organic lake sediments (sapropel) as a binder; sphagnum moss, flax fiber, and vermiculite as a filler. The main application of these composite materials is for sound absorption and moisture buffering, but since they contain bio-based binders and fillers, they also work as carbon storage. Within the framework of this work, a total of 100 samples of composite materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
(36 reference statements)
0
0
0
Order By: Relevance
“…In recent times, with the development of modern industry and air and road traffic, noise has become one of the countless factors affecting human health and the environment worldwide. Noise has become a major problem that causes harmful effects on human health, and combating it requires urgently finding the best solutions through increasingly restrictive regulations and legislation [ 1 , 2 ]. Lately, the improvement of living conditions by regulating noise in the fields of aviation (by reducing the interior noise of passenger aircraft), railways, automobiles and buildings is a requirement forced on industrial companies [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent times, with the development of modern industry and air and road traffic, noise has become one of the countless factors affecting human health and the environment worldwide. Noise has become a major problem that causes harmful effects on human health, and combating it requires urgently finding the best solutions through increasingly restrictive regulations and legislation [ 1 , 2 ]. Lately, the improvement of living conditions by regulating noise in the fields of aviation (by reducing the interior noise of passenger aircraft), railways, automobiles and buildings is a requirement forced on industrial companies [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Latvian researchers investigated the properties and sound absorption characteristics of composite materials made from sphagnum moss, flax fiber, vermiculite, and SP as a binder [17]. They demonstrated that the compressive strength of such composite materials was 0.1-0.29 MPa, whereas their bending resistance ranged between 0.2 and 0.42 MPa.…”
Section: Introductionmentioning
confidence: 99%
“…Although most of these fillers are bound with traditional phenol formaldehyde-based binders, other binders have also been proposed. Starch, sugar, sapropel, lignin, protein, etc., can be used as binders [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%